AB0533 Systematic Review: "Efficacy and Safety of Biological Therapy Compared To Immunosuppressive Therapy vs Placebo in The Treatment of Uveitis Associated with Behçet's Disease". (15th July 2016) - Urruticoechea-Arana, A.; Cobo-Ibáñez, T.; Villaverde Garcia, V.; Santos-Gόmez, M.; Diaz-González, F.; Fariñas-Padrόn, L.; Vargas-Osorio, K.; Calvo-Río, V.; Blanco Alonso, R.
Abstract : Background: Systemic treatments used in ocular involvement in Behçet's disease are corticosteroids, synthetic and biological immunosuppressants. Because of irreversible ophthalmic complications, it's a priority to know the efficacy of these drugs. Objectives: To analyze the efficacy and safety of biological therapy vs cyclosporine A (CyA), azathioprine (AZA) or placebo in reducing the rate of uveitis and improving the visual prognosis of Behçet's. Methods: A systematic search of literature on MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials was conducted from inception to July 2015.A hand search was performed by reviewing the references of the included studies and the international congress.Criteria for study selection:1)adults with Behçet's-uveitis, 2)Biological therapies, 3)placebo or active comparator with CyA or AZA, 4)outcome measures to evaluate effectiveness as a number (no) of recurrence of uveitis, visual prognosis, cystic macular edema, retinal vasculitis, vitritis, hypopyon, etc; and/or adverse events.Meta-analyses, systematic reviews, clinical trials and observational studies of>10 patients with comparator were included.The selection, review and evaluation of quality of the articles was independently conducted by 2 reviewers.The Oxford Level of Evidence scale was used to determine the quality of the studies. Results: Of 195 articles, 5 met the inclusion criteria:2retrospective observational studies and 3randomized clinical trials in 235 patients with Behçet and refractory uveitis.Age range was 12–69 years with male dominance, and follow up was 1–72 months.Evidence with infliximab (IFX) (2 studies) is weak and suggests more effective than CyA in reducing the rate of uveitis in short-term (6m) and more effective than CyA+AZA or methotrexate (MTX) to reduce the no. of retinal vasculitis relapse, and severe complications and to improve visual acuity in long term (LE4).The weak and insufficient evidence of rituximab (RTX) associated with MTX (1study) suggested similar efficacy to cyclophosphamide (CYM) associated with AZA, improving the total adjusted rate of disease activity without improvement in short-term visual acuity (6m)(LE 3b).Regarding secukinumab and daclizumab vs placebo (1 study respectively), the small but acceptable level of evidence suggests ineffectiveness in reducing relapses and in the improvement of visual acuity, with sparing effect on immunosuppressants in short-term for secukinumab (LE2a-2b). Available evidence reveals few significant adverse events. All studies could be applicable in clinical practice. Conclusions: With the limited evidence found, IFX appears to be safe and more effectiveness than CyA alone or in combination with other immunosuppressants in reducing short term uveitis relapse and the number of severe long-term complications.RTX is similar to CYM paired with AZA in improving rates of inflammatory activity in short term.Secukinumab as well as daclizumab is not effective in reducing relapses of uveitis but could spare immunosuppressants.The results of this review support the benefit of carrying out further well-designed comparative studies with IFX and RTX. Disclosure of Interest: None declared